HUBUNGAN ANTARA PROKRASTINASI DENGAN SELF REGULATED LEARNING PADA SISWA SMP - Arri Handayani; Dini Rakhmawati; Putri Oktavia Prayoga Putri (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study examines the relationship between academic procrastination and self-regulated learning among students of SMP X. The research employed a quantitative approach using a correlational method. The sample consisted of 205 eighth-grade students of SMP X selected through a saturated sampling technique. The research instruments included an academic procrastination scale and a self-regulated learning scale. The procrastination scale covered four indicators: delaying the initiation or completion of tasks, believing that postponement is preferable, repetitive procrastination behavior, and difficulty in making decisions. The self-regulated learning scale comprised indicators of goal setting and planning, seeking information, keeping records and monitoring, and environmental structuring. The normality test indicated that the data were normally distributed (p = 0.126). Pearson correlation analysis revealed a significant negative relationship (r = –0.561, p = 0.000), indicating that higher levels of self-regulated learning are associated with lower levels of academic procrastination. These findings highlight the important role of self-regulation in minimizing academic delay. This study provides a basis for educators and counselors to develop more targeted interventions and may serve as a reference for future academic support programs in schools.